EFFECTS OF SUPPLEMENTS ON MILK NITROGEN EFFICIENCY OF BUFFALO COWS - T. Seresinhe; H. J. D. Shamen; A. Manawadu; Marapana (Journal of Animal and Plant Sciences, 2012)
Effect of introducing supplements to cross bred buffalo cows (Murrah non descriptive, live weight 305 kg ±14, parity 3, stage of lactation 198-215 days) were tested in a field experiment. Treatments tested were natural herbage + low cost concentrate ration (GT; 686 g/ dry matter (DM) /head/day; rice bran 35%, urea 12%,molasses 45%, mineral mixture 8%- Treatment 1);natural herbage+farm made concentrate ration (FMC), 1800 g/DM /head/day; 40% coconut poonac, 40% rice bran, 18% soybean meal, 2% mineral mixture –Treatment 2); Treatment 2 + tree fodder (TF-480 g/DM/head/day) –Treatment 3; Treatment 1 + (TF) –Treatment 4 respectively. The cows in four treatments were allocated in a Latin square design. Average herbage intake was estimated as 5±0.21 kg /head/day with 21% DM and 9.21% crude protein. Milk yield was highest (P0.05) with cows in T4 followed by cows in T3 and T1 while cows in T2 had the lowest MNE. The contribution of low cost concentrate ration with balanced energy, nitrogen and minerals had beneficially influenced the overall nitrogen metabolism thus improving the MNE. Considering the cost and other associative practical applications in using high cost concentrate rations (41 Rs/kg) under small farmer conditions could be reduced with better results by incorporating low cost concentrate rations (17 Rs/kg) and freely available green leguminous forages.
Keywords: supplements; milk fat; total solids; milk nitrogen efficiency